Strategic Assessment of Indonesian E-Commerce Fashion Business - Natalie, Selva; Wandebori, Harimukti (Journal of Entrepreneurship, Business and Economics, 2018)
With the increasing number of Internet users in Indonesia, the number of Fashion E-Commerce Business also grows rapidly along with the fact that this industry has contributed greatly to the economic growth. However, the growing number of the incumbents apparently creates a major problem of competition within them and result in many challenges and obstacles to survive in the industry. In order to overcome these issues, a qualitative case study research was completed using a strategic management approach to aim at contributing a generalization theory in business strategy of SMEs. Both external and internal environmental scanning were made through secondary data, observation, and interviews to four businesses which assumed to represent the Fashion E-Commerce Business in Indonesia. EFAS and IFAS matrices were used, which followed by SFAS matrix that resulted in some strategies to be pursued and a conclusion suggesting a differentiation business strategy. It will result in uniquely owned strategies, complex external and internal linkages which are difficult to imitate by other players. With this, the business will have a sustainable competitive advantage to survive in the long term. Research paper Keywords: Business Strategy, Environmental Analysis, Fashion, SFAS, SMEs, Strategic Management Reference to this paper should be made as follows: Natalie, S., & Wandebori, H. (2018). Strategic Assessment of Indonesian E-Commerce Fashion Business, Journal of Entrepreneurship, Business and Economics , 6 (1), 1–35.